Pulmonary granulocyte influx and impaired alveolar macrophage adenylyl cyclase responsiveness in developing respiratory distress - J. G. C. van Amsterdam; R. M. J. L. van der Heijde; H. P. Grotjohan; F. D. Beusenberg (Mediators of Inflammation)
Alveolar macrophages have recently been postulated as being involved in the aetiology of adult respiratory distress syndrome (ARDS). To evaluate their role, basal cyclic AMP levels and responsiveness of adenylyl cyclase alveolar macrophages were determined at four intermediate stages of developing respiratory distress in piglets using a protocol with repeated lung lavage. Examination of alveolar cells recovered from the subsequent lavages reveals an influx of granulocytes (neutrophils and eosinophils) within 1 h of two intensive lung lavages. During the developing respiratory distress the basal cyclic AMPlevel of alveolar macrophages increases and adenylyl cyclase responsiveness to prostaglandin E2 (PGE2) and isoprelanaline diminishes. The previously observed impairment of macrophage activity can then be explained at a subcellular level.